Heritage languages at school: implications of linguistic research on bilingualism for heritage language teaching - Flores, Cristina (2019)
This paper discusses the implications of linguistic research on heritage bilingualism for heritage language teaching. It is argued that heritage speakers and second language learners have different instructional needs in the classroom because teaching of a heritage language is a case of native language instruction. Based on a number of comparative studies on heritage speakers and second language learners of European Portuguese, we show that heritage language acquisition is indeed different from L2 acquisition. The linguistic differences between the two groups of speakers can be accounted for by considering their age of onset of acquisition, the type of input they are exposed to, the type of knowledge they mainly rely on, the relative importance of cross-linguistic influence and the relevance of linguistic complexity and timing of acquisition. We argue that these findings have implications for heritage language teaching in the classroom, such as, for example, the necessity of appropriate diagnostic tools for determining the linguistic proficiency of heritage bilinguals, the provision of access to the standard variety by supplying adequate spoken as well as written input sources, the focus on properties of the language which are late acquired and only learned on the basis of formal instruction and the fostering of explicit linguistic knowledge.